Estudo fitoquímico e da atividade biológica de Zanthoxylum rhoifolium - Weber, Andréia Denise (2005)
Four previously known dihydrobenzophenanthridine alkaloids, Dihydrochelerythrine (39), Bocconoline (42), Chelerythrine (2) and 6- Acetonyldihydrochelerythrine (33), were isolated from the stem bark of Zanthoxylum rhoifolium, along with other three lignans and the triterpen Lupeol (11). One of the lignans was identified as being sesamine (114), common in Zanthoxylum and the other two, already known, called Kaerophyllin (117) and Gadain (120) belong to dibenzylbutyrolactones. However, Kaerophyllin (117) and Gadain (120) were isolated for the first time from the Zanthoxylum rhoifolium. The structures of these metabolites were determined, mainly through spectroscopic methods, such as Nuclear Magnetic Resonance Spectroscopy 1H e 13 C (COSY, HMQC e HMBC), mass spectrometry and through the comparison of the data obtained from the melting point and data from the literature. The pure compounds and the hexane and eterea acid fractions, as well as chloroform basic fraction were tested for antitumor activity with nine cultured human tumor cell lines in vitro: MCF-7 (breast), NCI-ADR (breast with phenotype of the drug-resistant), UACC-62 (melanoma), NCI-460 (lung), PCO-3 (prostate), HT29 (colon), OVCAR (ovary), 786-0 (kidney) e K-562 (leukemia). The dihydrobenzophenanthridine alkaloids and the fractions showed more active, inhibiting the growth and provoking the death of several cell lines. On the other hand, the lignans showed no significant activity, being that, gadain (120) showed citostatic activity for all lines, only in the largest concentration tested. Through antimicrobial activity assays against Gram-positive bacteria: Staphylococcus aureus, Staphylococcus epidermidis and Bacillus subtilius; ramnegatives: Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli and Salmonella setubal and fungi: Candida albicans, Candida dubliniensis, Sacharomyces cerevisiae and Cryptococcus neoformans, it was possible to observe that the alkaloids and the fractions were really active, mainly against bacteria. Chelerythrine (2) was the most active compound due to the growth inhibition of all the tested microorganisms, at the lowest concentration tested (0.15μg). The lignans were inactive against the tested microorganisms. The results found through the Microdilution Method showed that the alkaloid Chelerythrine presents a fungicide bacteriostatic property.